2022
DOI: 10.1186/s13071-022-05181-2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and transmissibility of Plasmodium ovale in Bagamoyo District, Tanzania

Abstract: Background Plasmodium ovale is a neglected malarial parasite that can form latent hypnozoites in the human liver. Over the last decade, molecular surveillance studies of non-falciparum malaria in Africa have highlighted that P. ovale is circulating below the radar, including areas where Plasmodium falciparum is in decline. To eliminate malaria where P. ovale is endemic, a better understanding of its epidemiology, asymptomatic carriage, and transmission biology is needed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…infections identified. There is precedent for this approach 17,25,31 , as low density parasitemia is characteristic of P. ovale spp. infections, making them challenging to detect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…infections identified. There is precedent for this approach 17,25,31 , as low density parasitemia is characteristic of P. ovale spp. infections, making them challenging to detect.…”
Section: Discussionmentioning
confidence: 99%
“…Decades of concentrated malaria control interventions have helped lower the national prevalence from 18% in 2008 to 7% in 2017 23 . The vast majority of malaria cases reported in Tanzania are attributed to P. falciparum 9,21 , although recent studies have also identified evidence of P. malariae, P. vivax , and P. ovale transmission 4,18,24,25 . Given widespread use of P. falciparum- specific HRP2-based RDTs for malaria diagnosis, the propensity for missed detection or misclassification of non-falciparum species in Tanzania is high, and large-scale, geographically representative studies to assess spatial distributions of these species are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Malaria transmission occurs throughout the year, with peaks typically during the long (March to June) and short (October to November) rainy seasons. Study data were collected as part of a large observational study called Project TranSMIT (Transmission of Submicroscopic Malaria in Tanzania) that prospectively screened and enrolled participants over three years for mosquito feeding studies and performed weekly follow-up over four weeks for a subset of participants with submicroscopic parasitemia (Markwalter et al, 2021; Tarimo et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Screened participants reported their age, gender, and village in which they reside. Approximately 200 μL of finger-prick blood was used to make thick and thin blood smears, perform a dual antigen HRP2 and pLDH RDT (rapid diagnostic test, SD Bioline), and create 2-3 dried blood spots (DBS) on Whatman 3MM filter paper for analysis by real-time polymerase chain reaction (PCR) targeting P. falciparum 18S rRNA as previously described (Markwalter et al, 2021; Tarimo et al, 2022). We previously determined the limit of detection (LOD) for the P. falciparum PCR test performed onsite as approximately 1-5 parasites/uL, which is more sensitive than both microscopy (approximately 50-500 parasites/uL) and RDT (approximately 100 parasites/uL), but not as sensitive as ultrasensitive PCR tests (Berzosa et al, 2018; Leski et al, 2020; Markwalter et al, 2021; Mfuh et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…This possibility is particularly salient in light of current malaria elimination goals stemming from the WHO Global Technical Strategy[9], which aims by 2030 to reduce the global malaria burden by 90% from 2015 levels. Non-falciparum malaria species have notably different biology than P. falciparum and are not necessarily controlled by the same measures, due to the potential for transmission by different vectors, differing seasonality[10], potentially earlier gametocytogenesis[1113], presence of hypnozoite stages/persistent infection[12,14], generally lower levels of parasite carriage/density[15,16], and greater asymptomatic infection and transmission[10].…”
Section: Introductionmentioning
confidence: 99%